A boat, a river, a circus (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In October 2023, a troupe made up of a university professor, a circus teacher and eight academics traveled up the Paraguay River towards the upper Pantanal to present a circus show for children who live in the flooded regions and study at the “escolas das águas”. The aim of this report is to recount the experience of giving pupils from two “escola das águas” on the Pantanal in the state of Mato Grosso the opportunity to watch a circus show and to briefly describe this encounter: children from the Pantanal waters and the circus.
Keywords: Pantanal; circus; Schools of the waters